Development and validation of the puppy blues scale measuring temporary affective disturbance resembling baby blues - Ståhl, Aada; Salonen, Milla; Hakanen, Emma; Mikkola, Salla; Sulkama, Sini; Lahti, Jari; Lohi, Hannes (Springer Nature, 2025)
It has been described that many puppy owners experience a state called puppy blues involving stress, worry, anxiety, strain, frustration, or regret. While puppy blues is a commonly used term among dog owners, the term is nearly nonexistent in scientific literature. In turn, analogous phenomenon, postpartum affective disturbance of infant caregivers, is well described in the literature. This study aimed to develop and validate the first questionnaire to evaluate puppy blues. The methodology involved generating scale items based on a qualitative review of 135 pilot survey responses from people who had experienced distress during the puppy period, conducting exploratory factor analysis for the final scale items from a dataset of 1801 answers from Finnish dog owners (92% women), and collecting test-retest data from 265 individuals to assess the consistency of the measurement of items and factor structure across time. In addition, we collected an independent sample of 326 owners of 1-2-year-old dogs who answered the survey both regarding puppy period and current moment. The results indicate that the scale is a valid and reliable tool for measuring dog owners' negative experiences and feelings related to puppyhood. We discovered three factors that describe different aspects of puppy blues: Frustration, Anxiety, and Weariness, which accounted for a significant proportion of the variance in puppy blues. The study demonstrated good internal consistency and consistency across two independent samples for the three identified factors. The test-retest reliability of the factors was good. Responses for the current timeframe compared to puppyhood experiences revealed significantly lower current scores across all factors for the current period, validating that the scale captures distress during puppyhood that diminishes over time. Interestingly, we found a fading affect bias where recollections of the experiences in the puppy period became more positive with time. Our findings shed light on the characteristics of puppy blues and provide a useful retrospective tool for measuring it.